Evaluation of Rice Quality Storage Stability: From Variety Screening to Trait Identification - Jinyu Tian; Guangmei Ji; Jiafeng Zhang; Danqiu Luo; Fang Zhang; Lijiang Li; Mingjin Jiang; Dawei Zhu; Min Li (Plants)
Rice, a staple global food crop, requires the maintenance of its quality stability during storage. This study aimed to screen rice varieties with high storage stability and elucidate their traits. Thirty-four widely cultivated varieties were selected to examine the changes in grain quality after one-year natural storage. The normalization method, hierarchical analysis, and cluster analysis were used to identify rice varieties maintaining their grain quality during storage. Meanwhile, the yield and its components, panicle traits, grain size, grain major component content, physiological indicators (such as antioxidant enzyme activity), and key growth stages were analyzed at rice maturity. The results showed that the processing, appearance, and eating quality of rice declined after storage. Specifically, the chalkiness degree increased significantly by 32.4%, while the cooked rice appearance, texture, and taste quality decreased significantly by 18.7%, 19.1%, and 14.2%, respectively. The grain quality storage stability was evaluated using a hierarchical analysis method based on the storage stability scores of the brown rice rate, milled rice rate, head milled rice rate, chalkiness degree, cooked rice appearance, cooked rice texture, and cooked rice taste. A judgment matrix was established, determining their corresponding weights of 0.0149, 0.0369, 0.0910, 0.286, 0.060, 0.148, and 0.364, respectively. Based on cluster analysis and the normalization method, these varieties were classified into three categories: high storage stability, intermediate storage stability, and low storage stability, accounting for 26.5%, 52.9%, and 20.6%, respectively. Finally, nine rice varieties with high storage stability were screened. The validation results of the principal component analysis also indicated the reliability of this result. Correlation analysis revealed that the storage stability of the rice grain quality was significantly and negatively correlated with the amylose starch content and malondialdehyde content. The average value and median value of the amylose starch content in high-storage-stability varieties are 10.7% and 6.99% lower than those in sensitive varieties, respectively. Therefore, the major feature of rice varieties with high storage stability is a low amylose starch content. This study provides valuable theoretical insights into the safe storage of rice grains and the selection and breeding of rice varieties with high storage stability.